Endothelial vulnerability and endothelial damage are associated with risk of Graft-Versus-Host Disease and response to steroid treatment - Dietrich, Sascha; Karamustafa, Suzan; Andrulis, Mindaugas; Hegenbart, Ute; Ho, Anthony Dick; Dreger, Peter; Luft, Thomas (Biology of blood and marrow transplantation, 2013)
There is accumulating evidence indicating that endothelial factors are involved in the pathogenesis of GVHD. We have recently shown that steroid-refractory, but not sensitive, GVHD is characterized by higher pretransplantation serum levels of angiopoetin-2 (ANG2), a hormone mediating endothelial vulnerability. To evaluate whether endothelial vulnerability is a risk factor for GVHD per se or becomes important only when noticeable GVHD is established, we measured ANG2 along with additional serum markers of endothelial stress, including soluble thrombomodulin (sTM), IL-8 (CXCL8), and hepatocyte growth factor (HGF), in patients with no, low-grade, or severe GVHD. Patients with refractory GVHD exhibited elevated serum levels of ANG2, sTM, HGF, and IL-8 posttransplantation compared with patients with sensitive GVHD and patients without GVHD. Pretransplantation ANG2 was the only growth factor correlated with the risk of refractoriness and mortality, and then only within the subset of patients who developed grade III-IV GVHD. In contrast, ANG2 was not predictive of GVHD or nonrelapse mortality (NRM) in patients with no GVHD or low-grade GVHD. These ﬁndings provide evidence that endothelial function plays an important role in the pathogenesis of steroid refractoriness in ongoing GVHD; however, endothelial vulnerability does not predict incidence of GVHD.